The impact of training and development on knowledge and skills enhancement of employees in Square Pharmaceuticals PLC - Husain, Taiyeb (Brac University, 2024)
An internship report submitted to the BRAC Business School, BRAC University in partial fulfillment of the requirements for the degree of [Bachelor of Business Administration], 2024.